Hybridization of Bornean Melastoma: implications for conservation of endemic plants in Southeast Asia. Issue 2 (3rd April 2019) - Cai, Yacheng; Wang, Fei; Tan, Guangwen; Hu, Zhenyang; Wang, Yongqi; Ng, Wei Lun; Wu, Wei; Liu, Ying; Zhou, Renchao
ABSTRACT: Hybridization has been found as a prevalent circumstance in nature, and it plays important roles in organismal evolution, speciation and even extinction. In this study, we focus on two species of the plant genus Melastoma, which has gone through a rapid species radiation during the last one million years. We successfully detected the hybridization signal between M. malabathricum and M. laevifolium in a suspected hybrid zone in Borneo, Malaysia, by sequencing five nuclear genes and two chloroplast fragments. Most individuals of the suspected hybrids were considered as first generation hybrids, while five individuals corresponded to advanced, early generations of hybrids. Although we did not find any introgression signal between M. malabathricum and M. laevifolium, it is necessary to pay more attention to assess the extinction risk of the species with restricted distribution, here M. laevifolium . This study is the first case of natural hybridization between Melastoma species in Southeast Asia, and more cases are waiting to be found in the field.